Comparison of the buccal mucosal bleeding time in dogs using 3 different‐sized lancet devices. (16th October 2013) - Aumann, Marcel; Rossi, Valentina; Le Boedec, Kevin; Diquélou, Armelle
Abstract : Background: The buccal mucosal bleeding time (BMBT) evaluates primary hemostasis in vivo. Three different‐sized lancet devices designed for people, Adult (A), Junior (J), and Newborn (N), can be used to perform the BMBT in dogs. Objectives: The aim was to compare BMBT using 3 different‐sized human lancet devices in dogs with varying platelet counts and hematocrits. Methods: The BMBT was measured in 46 client‐owned dogs (2 healthy, 44 suffering from various disorders) with varying platelet (Plt) counts and hematocrits, using the 3 devices successively in each dog, in a randomly determined order, over a 10‐ to 30‐minute period. Statistical analysis (ANOVA, Mann–Whitney U ‐test) was performed using commercial software. Results: BMBTs were significantly different between devices ( P  < .00001), and shorter with devices N and J compared with device A ( P  < .01). The BMBT was prolonged (> 210 s) in 10 dogs with device A and in 7 dogs each with devices J and N, respectively. Sixteen dogs had a Plt count < 200 × 10 9 /L (Reference interval 200–500 × 10 9 /L). Nine of these dogs had prolonged BMBT with device A, and 6 dogs with device J and device N, respectively. BMBT was longer in thrombocytopenic dogs with devices A and J ( P  < .016). Anemia without thrombocytopenia did not affect BMBT with any device. Conclusions: The BMBT is influenced by the size of the used device, with A resulting in the longest BMBT. Therefore, the type of device used to obtain the BMBT has to be specified for standardized results.